2008
DOI: 10.1200/jco.2007.13.2654
|View full text |Cite
|
Sign up to set email alerts
|

DNA Damage and Repair Capacity in Patients With Lung Cancer: Prediction of Multiple Primary Tumors

Abstract: Purpose Patients who survive one non-small cell lung cancer (NSCLC) are at higher risk of a second malignancy. Capacity to repair damaged DNA may modulate individual susceptibility to develop lung cancer. Therefore, we evaluated constitutive and induced DNA damage, and repair capacity, in patients with multiple NSCLC (cases) and compared the results to those obtained in patients with single NSCLC (controls). Methods One-hundred and eight cases and 99 controls matched by age, gender and time since diagnosis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
43
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 38 publications
1
43
1
Order By: Relevance
“…The study of Schmezer et al did not detect any significant difference between the levels of baseline DNA damage in lymphocytes of lung cancer patients and healthy individuals but found an increased sensitivity of lymphocytes to bleomycin and decreased DNA repair capacity in cancer patients [20]. The deficient DNA repair in lymphocytes of lung, head and neck cancer patients also has been shown by other researchers [4, 5, 8, 9]. It should be mentioned that the concentration of bleomycin (20 μg/ml) recommended by Schmezer et al, which we also used in our study, caused DNA damage at saturation level of the assay.…”
Section: Discussionmentioning
confidence: 82%
“…The study of Schmezer et al did not detect any significant difference between the levels of baseline DNA damage in lymphocytes of lung cancer patients and healthy individuals but found an increased sensitivity of lymphocytes to bleomycin and decreased DNA repair capacity in cancer patients [20]. The deficient DNA repair in lymphocytes of lung, head and neck cancer patients also has been shown by other researchers [4, 5, 8, 9]. It should be mentioned that the concentration of bleomycin (20 μg/ml) recommended by Schmezer et al, which we also used in our study, caused DNA damage at saturation level of the assay.…”
Section: Discussionmentioning
confidence: 82%
“…26 In the recent studies 24 hours of recovery time has been applied. 27,28 Shahidi et al 28 have reported that in healthy individuals no residual DNA damage has been observed after a 24-hour repair incubation of leukocytes exposed to radiation. In the present study, an incubation time of 24 hours was chosen to guarantee the completion of repair.…”
Section: Discussionmentioning
confidence: 97%
“…It has been reported that interindividual variation in DNA repair capacity may lead to increased predisposition to cancer 29. Abnormal mutagen sensitivity found in studies that indirectly assessed DNA repair capacity has been found in patients with head and neck, colorectal, and non-small-cell lung cancers, as well as in patients with multiple primaries of similar malignancies 30. In the present analysis, cancer survivors who were smokers had a higher risk of multiple primaries compared with nonsmokers, particularly for lung, colorectal, and prostate cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with hereditary nonpolyposis colorectal cancer with multiple primaries have an increased frequency of mismatch repair genes, such as hMSH2 and hMLH1 , leading to microsatellite instability 33. Mutagen sensitivity, found in studies that indirectly assessed DNA repair capacity, tends to occur in patients with head and neck, hereditary nonpolyposis colorectal, and non-small-cell lung cancers 30. In the present study, a strong family history of cancer reflecting a close relationship between first-degree relatives was statistically more common in patients with multiple primaries, especially those with three or more primaries, and in those with metachronous primaries, highly suggestive of inherited cancer predisposition gene mutations, especially among Caucasian patients.…”
Section: Discussionmentioning
confidence: 99%